INTERACTIVE METHODS OF TEACHING RUSSIAN LANGUAGE (FOREIGN EXPERTISE VS. CLASSICAL METHODS OF TEACHING) - N.F, Azimova; S.Yo, Sayidova (The journal of contemporary issues in business and government, 2021)
Today it is impossible to imagine the educational process, including in professional education, without the use of interactive forms and teaching methods. Interactive learning contributes to more effective perception and consolidation of the material received, allows you to develop the personal qualities of the student, to form his professional abilities and capabilities. The use of interactive teaching methods in the classroom in Russian as a foreign language contributes to an increase in the formed communicative abilities of foreign students, and also activates the cognitive interest in learning the language.